Kinematic and aerodynamic modelling of flapping wing ornithopter. - Djojodihardjoa, Harijono; Ramli, Alif Syamim Syazwan; Wiriadidjaja, Surjatin (2012)
A generic approach is carried out to model the kinematics and aerodynamics of ornithopter to mimic flapping wing to produce lift and thrust for hovering and forward flight, by considering the motion of a three-dimensional rigid thin wing in flapping and pitching motion with phase lag. Basic Unsteady Aerodynamic Approach incorporating salient features of viscous effect and leading-edge suction will be utilized. Parametric study is carried out to reveal the aerodynamic characteristics of ornithopter flight characteristics and for the analysis of various selected simple models in the literature, in an effort to develop a flying ortnithopter model. Further considerations will be given to other important parameters such as flapping frequency and wing geometry for well conceived formulations with realistic and workable assumptions and limitations.